2019
DOI: 10.21831/ltr.v18i3.26494
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ Politeness Strategies in Efl Classroom With Multicultural Background

Abstract: The choice of words used by the lecturer such as politeness strategies in the classroom interaction is very important, not only for controlling the classroom but also for the process of acquiring the language itself. This study aimed to investigate lecturer’s politeness strategies in criticizing teaching performance of students with multicultural backgrounds in a microteaching class. This qualitative study was conducted with the students from multicultural backgrounds. The subject of this study was a lecturer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Purnomo (2020) in his study about politeness strategies used by teachers in EFL classes revealed that positive politeness becomes the most frequently employed. It implied that the lecturer mostly applied positive politeness in criticizing the students, in order to save the students' face, get closer and give more positive feedback (Heriyawati, Siba and Sulistyo, 2019). In term of the differences on the language usage between male and female, Syafrizal and Putri (2020) who conducted a politeness study on university students showed that women were more respectful than male students in general.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Purnomo (2020) in his study about politeness strategies used by teachers in EFL classes revealed that positive politeness becomes the most frequently employed. It implied that the lecturer mostly applied positive politeness in criticizing the students, in order to save the students' face, get closer and give more positive feedback (Heriyawati, Siba and Sulistyo, 2019). In term of the differences on the language usage between male and female, Syafrizal and Putri (2020) who conducted a politeness study on university students showed that women were more respectful than male students in general.…”
Section: Previous Studiesmentioning
confidence: 99%
“…It can be proven that all politeness strategies are used by both lecturers and students. In addition, the results of the study also illustrate that communication and interaction between lecturers and students are very diverse although some studies report that lecturers tend to use positive politeness strategies with students (Heriyawati et al, 2019;Nugrahanto & Hartono, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…It is undeniable that interaction becomes pivotal process in teaching and learning activity. One of the most important aspects of teaching and learning process in an EFL classroom is the interaction that occurs between teachers and students (Hai & Bee 2006;Forman 2012;Heriyawati 2019;Nasir et al 2019;Eisenring & Margana 2019;Havik & Westergard, 2020;Rahayu & Syahrizal 2020;Jayalath: 2021, Yasin, et al 2022. According to Brown (2007) interaction as a cooperative mental, emotional, or intellectual exchange between a teacher and students or between students themselves that has a reciprocal impact on both sides.…”
Section: A Introductionmentioning
confidence: 99%